From Renunciation to Nirvana and Beatitude: What Is Common in Buddha and Christ? - Bhandari, Sabindra Raj (Prithvi Academic Journal, 2021)
This article explores the confluence in the ideas that Buddha postulated in the Dhammapada and Christ in the gospels of Mathew, Mark, Luke and John in the New Testament. In spite of the differences in their context, arena, and even in trends and tenets, they both project that the renouncement in action lead the worldly affairs to the realm of spiritual illumination. Both the Dhammapada and the four gospels from the New Testament clearly proclaim that subtraction of the ego along with the pursuit of wisdom eventually open the path of inner evolution for redemption—Nirvana and Beatitude. Likewise, the concepts of Bodhisattva and Messiah have similar mission to redeem the humanity. All these concepts invite a new revisiting to qualify them, adding a new in-depth insight. This fresh revisit widens new dimensions to view the meeting points between the seemingly diverse religious philosophies. Therefore, this paper has applied the qualitative approach to the ideas from the divine creations—the Dhammapada and the gospels of Mathew, Mark, Luke and John from the New Testament.